THE INFLUENCE OF PLACEMENT AND WORK ETHIC ON EMPLOYEE PERFORMANCE AT PT. AIRINDO MEDICAL CENTER, JAKARTA - Shela Indah Savitri; Indra Januar Rukmana; Syawaludin Syawaludin (SEAN Institute, 2023)
This study aims to determine the partial and simultaneous effect of placement and work discipline on employee performance at PT. Airindo Sentra Medika Jakarta. The research method that will be used in this study is the associative method with a quantitative approach, using a saturated sample with a total population of all employees of PT. Airindo Sentra Medika Jakarta as many as 60 respondents. The analytical method used in this research is simple and multiple linear regression analysis, coefficient of determination analysis R2, and hypothesis analysis t test (partial) and f test (simultaneous). Based on the results of the research, placement has a significant effect on employee performance with the regression equation Y 38.291 + 0.050 X1. Hypothesis test obtained t count t table or (0.447 < 1.671). Thus, H0 is rejected and Ha is accepted, meaning that there is a significant influence between placement on employee performance. Work ethic has a significant effect on employee performance with the regression equation Y 18.389 + 0.556 X2. Hypothesis test obtained t count t table or (4,861 > 1,671). Thus H0 is rejected and Ha is accepted, meaning that there is a significant influence between work discipline on employee performance. Placement and work discipline have a significant effect on employee performance with the regression equation Y 14.578 + 0.087 X1 + 0.565 X2. The value of the coefficient of determination is 30.0% while the remaining 70% is influenced by other factors. Testing the hypothesis obtained the value of F arithmetic F table or (12,215 > 4.00). Thus H0 is rejected and Ha is accepted. This means that there is a simultaneous significant influence between placement and work ethic on employee performance at PT. Airindo Sentra Medika Jakarta. By using SPSS Version 26.